Implications and Considerations of Dental Materials in MRI: A Case Report and Literature Review - Brenton J. Wilson; Phoebe E. O’hare; John Zacariah (Case Reports in Dentistry)
Magnetic resonance imaging (MRI) has an increasing role as a diagnostic imaging modality. Dental materials have important implications on the use of MRI as a diagnostic imaging modality. A case of a dislodged crown while in an MRI machine prompted a review of the literature for the implications and considerations of dental materials with magnetic resonance technology. An understanding of the basic physics involved in magnetic resonance is required to appreciate the relevance of dental materials in an MRI scanner. This case report supported by a literature review recommends assessing a patient’s crown retention prior to and after MRI scanning.